Mathematical principles of the Internet : Volume 1 : Engineering fundamentals - Bhatnagar, Nirdosh (Boca Raton : CRC Press, Taylor & Francis Group, 2019)
The purpose of these books is to provide mathematical principles of Internet engineering. They do not aim to provide all of the mathematical foundations upon which the Internet is based. Rather, they cover a partial panorama and key principles. The book is divided into two parts. Volume 1 explores Internet engineering. The supporting mathematics is covered in Volume 2. The chapters on mathematics complement those on the engineering episodes. An effort has been made to provide justification and informal proofs as much as possible. Each chapter also begins with a portrait and a brief account of the work of a prominent mathematician/scientist/engineer
Volume 1 : Introduction1. Information Theory 2. Algebraic Coding Theory 3. Cryptography 4. Internet Traffic 5. Dynamics, Control, and Management of Internet Congestion 6. Queueing Theory 7. Stochastic Structure of the Internet and the WorldWide Web 8. Graph-Theoretic Algorithms 9. Game Theory and the Internet 10. Internet Economics 11. Data Mining, and Knowledge Discovery12. Quantum Computation, Communication, and Cryptography
Includes bibliographical references and index.
ESS
Parama
Keywords: Internet -- Mathematics; Computer scienc -- Mathematics; Internetworking (Telecommunication) -- Mathematics